Caracterización fisicoquímica de la cáscara de banano variedad gros michel (musa acuminata, aaa group) - Freire Herrera, Anthony Benigno; Molina Cevallos, Genesis Gabriela (Machala: Universidad Técnica de Machala, 2023)
This undergraduate thesis presents a comprehensive investigation into the chemical composition of banana peels (Musa Acuminata) across 3 distinct ripeness levels. The primary objectives of this research were to assess the chemical quality of these peels, gauge their antioxidant capacity, and identify their potential as functional ingredients. Through chemical analyses, significant findings were obtained. The pH values were measured as 5,18 ± 0,07, 4.64 ± 0,13, and 5,18 ± 0,03 for ripeness indices E2, E6, and E7, respectively. Additionally, the soluble solids content (SST) exhibited values of 1,43 ± 0,15, 11,7 ± 0,95, and 15,83 ± 0,64 for the same ripeness levels. In the bromatological study, the content of ash, protein and fat was determined for both the samples with and without antioxidant treatment, respectively. The mineral content displayed notably high levels, with sodium (71.2 and 761), Fe (21.2 and 24.8), Zn (11.2 11.6) and K (3.34 and 3.45), for samples with and without antioxidant treatment, respectively. Furthermore, the study delved into the influence of antioxidant treatment and ripeness index on phenolic content and antioxidant capacity. The Folin-Ciocalteu method was employed to assess total phenolic content, while the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and the ferric reducing antioxidant power (FRAP) assay were used to quantify antioxidant capacity. Remarkably, this research revealed that the application of antioxidant treatment, coupled with consideration of the ripeness index (E7), facilitated the extraction of phenolic compounds (47,71 ± 2,64mg EAG/g). Moreover, a substantial increase in antioxidant capacity was observed in both the DPPH assay (116,76 ± 0,17 mg TEAC/g) and the FRAP assay (90,53 ± 3,76 mg TEAC/g). In this way, it was demonstrated that the antioxidant treatment and the advancement of ripening are factors that significantly influence the content of phenolic compounds and the antioxidant capacity of banana peel. The study showed that banana peels (Musa Acuminata) can be used as a functional ingredient due to its high antioxidant activity.
En la presente investigación se evaluó la composición química de las cáscaras de banano (Musa Acuminata) en tres niveles de maduración, con la finalidad de conocer su calidad química, capacidad antioxidante e identificar su potencialidad como ingrediente funcional. Mediante el análisis químico se determinó el valor de pH (5,18 ± 0,07, 4,64 ± 0,13 y 5,18 ± 0,03) y SST (1,43 ± 0,15, 11,7 ± 0,95 y 15,83 ± 0,64) tanto en el índice de maduración E2, E6 y E7 respectivamente. El análisis bromatológico determinó el contenido de cenizas, proteínas y grasa en muestras con y sin tratamiento antioxidante. La cuantificación de minerales mostró niveles altos de Na (71.2 y 761), Fe (21,2 y 24,8), Zn (11,2 ± 11,6) y K (3,34 y 3,45) tanto para las muestras con y sin tratamiento antioxidante. Así mismo se determinó la influencia del tratamiento antioxidante y el índice de maduración sobre el contenido fenólico y capacidad antioxidante de las cascaras de banano. En este sentido, para evaluar el contenido de fenoles totales se empleó el método de Folin-Ciocalteu y para cuantificar la capacidad antioxidante se usó la técnica 2,2-difenil-1-picrilhidrazilo (DPPH) y el poder antioxidante de la reducción férrica (FRAP), encontrándose que la aplicación del tratamiento antioxidante y el hecho de trabajar con cascaras de banano en nivel de madurez 7, se favorece la extracción de compuestos fenólicos (47,71 ± 2,64 mg EAG/g) e incrementa capacidad antioxidante de las muestras evaluadas tanto por el método de ensayo DPPH (116,76 ± 0,17 mg TEAC/g) como en el ensayo FRAP (90,53 ± 3,76 mg TEAC/g). De esta manera se demostró que el tratamiento antioxidante y el avance de la maduración son factores que influyen significativamente sobre el contenido de compuestos fenólicos y la capacidad antioxidante de la cascara de banano. El estudio evidenció que las cáscaras de banano (Musa Acuminata) pueden ser utilizadas como ingrediente funcional debido a su alta actividad antioxidante.
Keywords: CASCARAS DE BANANO; CAPACIDAD ANTIOXIDANTE; COMPUESTOS FENOLICOS; INDICE DE MADURACION